Answer :


[R2’ = (1/2)R2]


[R2’ = R2 - R3]


[R1’ = R1 - R3]


[R3’ = 2R3]


= ( - 14){(2 × 13) - (2 × 12)} - 5{(2 × )– ( - 3) × 13} - 5{( - 3) × 12 - 2 × }


[expanding by the first row]


= - 14 × (26 - 24) - 5(81 + 39) - 5( - 36 - 81)


= - 14 × 2 - 5 × 120 - 5 × ( - 117) = - 28 - 600 + 585 = - 43


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers